Effects of a Monoclonal Antibody to Glycoprotein IIb/IIIa (P256) and of Enzymically Derived Fragments of P256 on Human Platelets - Stuttle, A W J; Powling, M J; Ritter, J M; Hardisty, R M (Thrombosis and Haemostasis, 1991)
The anti-platelet monoclonal antibody P256 is currently undergoing development for in vivo detection of thrombus. We have examined the actions of P256 and two fragments on human platelet function. P256, and its divalent fragment, caused aggregation at concentrations of 10−9−3 × 10−8 M. A monovalent fragment of P256 did not cause aggregation at concentrations up to 10−7 M. P256–induced platelet aggregation was dependent upon extracellular calcium ions as assessed by quin2 fluorescence. Indomethacin partially inhibited platelet aggregation and completely inhibited intracellular calcium mobilisation. Apyrase caused partial inhibition of aggregation. Aggregation induced by the divalent fragment was dependent upon fibrinogen and was inhibited by prostacyclin. Aggregation induced by the whole antibody was only partially dependent upon fibrinogen, but was also inhibited by prostacyclin. P256 whole antibody was shown, by flow cytometry, to induce fibrinogen binding to indomethacin treated platelets. Monovalent P256 was shown to be a specific antagonist for aggregation induced by the divalent forms. In–111–labelled monovalent fragment bound to gel-filtered platelets in a saturable and displaceable manner. Monovalent P256 represents a safer form for in vivo applications